Do Consumers Shop in Tiktok? The TAM Perspective - Nguyen Thanh Luan (ZBW - Leibniz Information Centre for Economics, 2024)
Today's society is increasingly developing, leading to the improvement and advancement of technology, which has made the shopping needs of consumers more enhanced. The fact that consumers choose to shop online on e-commerce platforms is gradually becoming more popular and diverse. Especially not Shoppe, Lazada or Tiki but recently Tiktok is also gradually becoming a place for people to entertain, shop and it is quite popular. This creates a lot of opportunities and challenges as well as promotes the creativity and potential of businesses. Therefore, this study was created with the aim to find out and explore the factors affecting the intention to shop online on Tiktok of consumers in Ho Chi Minh City through the Public Acceptance Model Theory. Turmeric (TAM). The research method used is conditional sampling. A questionnaire will be used to collect data from consumers who often shop online to clarify the factors affecting their decision on Tiktok, namely Perceived usefulness (PUF), Perceived ease of use (PEU), Acceptance attitude (ACA), Consumer confidence (CCF), Subjective standards (SJS), Intention to use (ITU). The experts checked through the questions established through the face value and the content value to ensure the validity and reliability of the survey tool. The findings show the difference in the positive impact of surrounding factors on consumers' shopping intention on Tiktok social network in Ho Chi Minh City.
Keywords: 650; Online shopping; Tiktok social network; consumer trust; TAM